Implementation of physical education based on Community Based Tourism (CBT) through surfing activities in Cimaja, Sukabumi: Integrative strategies in outdoor education and strengthening students' character - Ferdiansyah, Feri; Rizal, Rony M.; Rohendi, Aep (ARKA INSTITUTE, 2025)
This research aims to integrate the Community Based Tourism approach in physical education through surfing activities at Cimaja Beach, Sukabumi. Using a descriptive qualitative method, this study examines how outdoor physical activities can be implemented contextually to develop motor skills, form character, and empower local communities. The data collection technique involves in-depth interviews, participatory observations, Focus Group Discussions, and documentation studies. The results of the study show that surfing activities significantly improve the balance, coordination, and physical strength of students. In addition, this activity also instills the values of courage, sportsmanship, and cooperation, in accordance with the principles of affective learning and experiential learning. The involvement of local communities in training and facilitation also enriches the social and cultural dimensions of learning, creating a participatory and contextual educational model. However, this study also found a number of obstacles such as lack of infrastructure, limited tools, and low teacher competence in outdoor education. Overall, the CBT-based physical education model contributes to the achievement of basic competencies in the PJOK curriculum, as well as being a means of inclusive social transformation. This model is recommended to be replicated in other areas with natural tourism potential, as a meaningful, sustainable, and community-based outdoor education innovation.